Q. 155.0( 5 Votes )
If a = 3x – 5y, b
(i) a + b – c = 3x – 5y + 6x + 3y-2y + 4x
⇒ a + b – c = 13x - 4y
(ii) 2a–3b + 4c = 2(3x – 5y) + 3(6x + 3y)-4(2y – 4x)
⇒ 2a–3b + 4c = 6x-10y + 18x + 9y-8y + 16x
⇒ 2a–3b + 4c = 40x-9y
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation